Analysis Of The Influence Of Ceo By Gender On Tax Aggressiveness In Manufacturing Companies Listed On The Indonesian Stock Exchange - Jasmine Aziizah Hermawan (Universitas Internasional Batam, 2024)
The study aimed to determine the effect of CEO gender variables, CEO age, as well as CEO gender reassignment on tax aggressiveness. Taxes are one of the burdens for companies that will reduce the company's profits. A company tends to do tax evasion to reduce its tax burden through a variety of means. Thus, companies are becoming more aggressive towards taxes. Tax aggressiveness is an action taken by companies to engineer taxable income through tax planning in a legal (tax avoidance) or illegal (tax evasion). This research is applied with cross sectional and time series methods. The technique used in sampling data in this study is purposive sampling. This method is done by selecting a research sample through certain considerations or criteria, based on the purpose of the research. The sample population in this study is the annual report and financial statements of manufacturing companies listed on the Indonesia Stock Exchange that have been audited in 2017 to 2020 with a total of 193 companies. Information about the annual report data and financial statements is obtained from the site contained on the Indonesia Stock Exchange, namely www.idx.co.id.